2014
DOI: 10.3390/ijerph110606314
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Childhood Lead Exposure through GIS: A Review of the Recent Literature

Abstract: Childhood exposure to lead remains a critical health control problem in the US. Integration of Geographic Information Systems (GIS) into childhood lead exposure studies significantly enhanced identifying lead hazards in the environment and determining at risk children. Research indicates that the toxic threshold for lead exposure was updated three times in the last four decades: 60 to 30 micrograms per deciliter (µg/dL) in 1975, 25 µg/dL in 1985, and 10 µb/dL in 1991. These changes revealed the extent of lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Hazard indices for children were higher than those for adults meaning that children would experience more non-cancer risks than adults. Young children absorb chemicals four times more than adults (Akkus & Ozdenerol, 2014). Similar observations have been reported (Guerra et al, 2012;Bamuwamye, Ogwok, & Tumuhairwe, 2015).…”
Section: Human Health Risk Assessmentsupporting
confidence: 77%
“…Hazard indices for children were higher than those for adults meaning that children would experience more non-cancer risks than adults. Young children absorb chemicals four times more than adults (Akkus & Ozdenerol, 2014). Similar observations have been reported (Guerra et al, 2012;Bamuwamye, Ogwok, & Tumuhairwe, 2015).…”
Section: Human Health Risk Assessmentsupporting
confidence: 77%
“…Age, race/Hispanic origin, and urbanization have been associated with BLLs in previous studies ( Akkus and Ozdenerol 2014 ; Wheeler and Brown 2013 ). Age in years was recorded at the time of the NHANES household interview and was used as a discrete variable and dichotomized as 1–2 versus 3–5 y of age because CMS has required universal screening by Medicaid of children at 1 and 2 y of age.…”
Section: Methodsmentioning
confidence: 71%
“…In the absence of effect modification by age, age-adjusted prevalence ratios would represent the association between WIC/Medicaid status and high BLL for all children in the study, including children in the 1- to 2-y age range. Race/Hispanic origin and urbanization of residence have also been associated with BLLs ( Akkus and Ozdenerol 2014 ; Wheeler and Brown 2013 ). Therefore, we repeated models after adjusting for these factors in addition to age and compared the resulting estimates to those from the primary model.…”
Section: Methodsmentioning
confidence: 99%
“…Lead (Pb) is a widespread environmental heavy metal toxicant that exerts irreversible effects on children’s cognitive function, impairing learning and memory 1 , decreasing intelligence quotient 2 , and increasing aggression and crime rates 3 . Lead can enter the human body via skin, respiratory system and/or gastrointestinal tract 4 , and the regulatory blood-lead-level (BLL) thresholds for childhood Pb poisoning have gradually decreased, from 30–60 μg/dl in 1975 to 5 μg/dl in 2012 5 . However, recent studies have shown that BLL as low as 1–5 μg/dl poses a risk for neurocognitive effects in the fetus and newborn 6 .…”
Section: Introductionmentioning
confidence: 99%